Metallic nanoparticles as advanced tools in radiation dosimetry and radiotherapeutic therapy - Lima, Iara Souza (2023)
Noble metal nanoparticles, such as gold (AuNPs) and platinum (PtNPs), have proven adaptable and effective in a variety of scientific fields. Significant candidates for biomedical applications, they are characterized by precisely controlled synthesis, modifiable properties, and adaptability. In the context for dosimetry application, AuNPs exhibit promise due to their unique optical and surface properties, as well as their high atomic number, which significantly increases the probability of interaction with ionizing radiation. The insertion of AuNPs into a gelatinous Fricke-Xylenol-Orange (FXO-f) gel matrix noticeably enhances dosimetric sensitivity. This heightened sensitivity was assessed through optical tomography and magnetic resonance imaging. Similarly, PtNPs, covered with poly (vinyl alcohol) (PVA) for stability, were investigated. After thorough optimization of the synthesis process, these nanoparticles exhibited non-cytotoxicity towards fibroblast cells. The primary focus of this study was to improve the PtNPs synthesis techniques. Additionally, the study explored the application of PtNPs in electron spin resonance (ESR) dosimetry with alanine, aiming to enhance dosimetric sensitivity through the increased concentration of free radicals induced by ionizing radiation. Furthermore, PtNPs, owing to their elevated atomic number, which amplifies the probability of interaction with ionizing radiation, demonstrated their potential in inducing the death of cancer cells, specifically B16F10 melanoma cells. Therefore, these studies, covers two chapters of this thesis (Chapters III and IV), proposing an optimized synthesis and non-toxic NPs when not irradiated and their potential applications for radiation dosimetry and cancer therapy. In conclusion, this thesis explores the multifaceted applications of noble metal nanoparticles, namely AuNPs and PtNPs, in radiation dosimetry and cancer treatment. The research results provide insights into opportunities for innovation and advancement in the application of these nanomaterials, with a specific focus on oncology therapy and radiation dosimetry.